Booked - Alexander, Kwame; Anyabwile, Dawud (New York : Clarion Books, 2022)
Twelve-year-old Nick is a football-mad boy who absolutely hates books. In this follow-up to the Newbery-winning novel The Crossover, football, family, love, and friendship take centre stage as Nick tries to figure out how to navigate his parents' break-up, stand up to bullies, and impress the girl of his dreams. These challenges - which seem even harder than scoring a tie-breaking, game-winning goal - change his life, as well as his best friend's. This energetic novel-in-verse by the poet Kwame Alexander captures all the thrills and setbacks, the action and emotion of a World Cup match.
5-8.
English.
Keywords: Children's stories. -- Graphic novel; Stories in rhyme